PERAN LEMBAGA PERKREDITAN DESA (LPD) DESA ADAT DUDA DALAM PELAKSANAAN PROGRAM KELAYUSEKARAN SERTA BEASISWA - Jati, Ni Nengah Ayu Sri; Wijaya, Komang Adi Sastra; Wirantari, I Dewa Ayu Putri (CITIZEN CHARTER, 2023)
“The Village Credit Institution (LPD) is a financial institution owned” by traditional villages which is one source that can assist community development and empowerment. The establishment of the LPD is inseparable from the Bali Provincial “Regulation No. 8 of 2002 concerning Village Credit Institutions to support” the “economic” development of rural communities. In managing the profits obtained by the LPD Adat Duda, they carry out the kelayusekaran program and the scholarship program. “The research method used is descriptive qualitative method,the interview, observation and, documentation” techniques. The findings show that the active role of LPD Adat Duda in the implementation of the welfare and scholarship programs can be seen from several indicators of the implemented role theory, such as “the interpersonal roles, informational roles and, decisional roles” that have been well implemented. In conveying information to the community, the role of the Duda Traditional Village LPD is still lacking, there is a need for regular socialization, and in the implementation of the scholarship program, further coordination is needed. Keywords: Village Credit Institution (LPD), Kelayusekaran and Scholarship Program, Role of LPD, Role Theory.